2020
DOI: 10.3389/fncel.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Method to Isolate and Culture Adult Porcine, Rats and Mice Müller Glia in Order to Study Retinal Diseases

Abstract: Müller cells are the predominant glial elements in the retina, extending vertically across this structure, and they fulfill a wealth support roles that are critical for neurons. Alterations to the behavior and phenotype of Müller glia are often seen in animal models of retinal degeneration and in retinal tissue from patients with a variety of retinal disorders. Thus, elucidating the mechanisms underlying the development of retinal diseases would help better understand the cellular processes involved in such pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…We have recently established a method to purify and culture adult Müller glia cells from mouse, rat and pig retinas, and we have previously shown that cultured murine Müller glia cells express GFAP, Glutamine Synthetase (GS), p75 NTR , and Cralbp. Flow cytometry indicated that >94% of all the cells in these cultures express p75 NTR [ 43 ]. In order to further characterize our Müller glia culture system, we used a combination of markers normally expressed in Müller glia cells, including the cytoskeletal protein Vimentin ( Figure 2 A,A’, green) and the transcription factors Lhx2, Pax6, and Sox2 ( Figure 2 B–D, red).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently established a method to purify and culture adult Müller glia cells from mouse, rat and pig retinas, and we have previously shown that cultured murine Müller glia cells express GFAP, Glutamine Synthetase (GS), p75 NTR , and Cralbp. Flow cytometry indicated that >94% of all the cells in these cultures express p75 NTR [ 43 ]. In order to further characterize our Müller glia culture system, we used a combination of markers normally expressed in Müller glia cells, including the cytoskeletal protein Vimentin ( Figure 2 A,A’, green) and the transcription factors Lhx2, Pax6, and Sox2 ( Figure 2 B–D, red).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of MIO-M1, it has been observed that these cells express marker genes of neural progenitors as well as postmitotic neuronal cells and various opsins [ 42 , 43 ]. Thus, primary cells are often considered as more physiologically similar to in vivo cells [ 44 ]. Therefore, we also analyzed primary equine RMG.…”
Section: Discussionmentioning
confidence: 99%
“…The culture medium was changed every 4-5 days and cells were passaged biweekly at a ratio of 1:3. Müller cells were identified by their characteristic bipolar morphology and immunostained with glutamine synthetase and glial fibrillary acidic protein (data not shown) (25). The purity of Müller cells was >90% after 2-3 passages.…”
Section: Methodsmentioning
confidence: 95%